Scientific Miraculous in Holy Quran – Terminology Issue - Charmand, Mohamad Mostafa (Journal of Humanities & Social Sciences, 2024)
This is a dialectical analytical study in the art of scientific miracles in the Holy Qur'an, which was commonly mentioned in this century among people, and a statement of the validity of the naming of modern scientific discoveries and the approval of some of them to the texts of the Holy Qur'an with this name, in a gesture of the importance of considering scientific methods in this section, and lest the speech be a kind of fabrication between science and an overlap of knowledge, and the study has shown a party of the types of science and methods of inference, to prove through the scientific method if the name and its intended meanings Correct in the terminology of scientists, relying on the analytical and dialectical method, with the aim of putting this art on disciplined scientific foundations, within its own framework so that it does not exceed its place, and under its corresponding term, the sciences are different, and in order to know the status of this science was this research. She also explained the types of miracles in the Holy Qur'an, and what is the choice of Islamic scholars in that, noting that speech in this section needs controls and foundations, pursuing accuracy in speech, and objectivity in criticism, without boring lengthening, nor abbreviation disruptive, in order to control speech in this art and be fully aware of it, so it improves our use of it, and we presented it with what we aim for and wish in the field of calling to God, from introducing people into this religion, And to document Muslims with their beliefs and faith with certainty.
Keywords: Holy quran; scientific miraculous; miracle definition; Quran and Science